Pengembangan kompetensi profesional guru PAI melalui pemanfaatan teknologi informasi - Sutisna, Usman; Elkarimah, Mia Fitriah; Asma, Fery Rahmawan (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2020)
Teachers are at the forefront of school, and students' development must have various competencies, namely pedagogical, personal, social, and professional competencies. In professional competence, educators must take advantage of information and communication technology to communicate and develop themselves. This community service activity aims to support the educator in gaining professional competence. Significantly to improve Islamic Religious Education (PAI) teachers' professional competence and encourage the realization of good learning, especially in making questions and materials that require Arabic Al-Qur'an components in it. Thirty-five religious teachers from 34 Elementary School Education units, both public and private, who are members of the KKGPAI (Islamic Religious Education Teachers Working Group) throughout the Setiabudi sub-district attended this training. The training method uses lectures and demonstrations or direct practice. The community service team's task is to help teachers who initially do not understand and cannot make Arabian font or language with computers. Therefore, through in-teacher training, Â the educator can make PAI questions and written works in Arabic using computers. As the results of community service activities in general, religious teachers who are members of the KKPAI of Setiabudi district have made PAI questions in Arabic using a computer application